2017
DOI: 10.1038/emm.2017.226
|View full text |Cite
|
Sign up to set email alerts
|

Dual modulation of human hepatic zonation via canonical and non-canonical Wnt pathways

Abstract: The hepatic lobule is divided into three zones along the portal-central vein axis. Hepatocytes within each zone exhibit a distinctive gene expression profile that coordinates their metabolic compartmentalization. The zone-dependent heterogeneity of hepatocytes has been hypothesized to result from the differential degree of exposure to oxygen, nutrition and gut-derived toxins. In addition, the gradient of Wnt signaling that increases towards the central vein seen in rodent models is believed to play a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 42 publications
(58 reference statements)
8
64
0
Order By: Relevance
“…A key role of Wnt signaling for the maintenance of liver structure and regeneration is well established from murine liver 12,[27][28][29][30] . A recent analysis indicated that Wnt pathways are also involved in human liver zonation 19 . Our deep integrated datasets allowed a deeper look into the putative role of pericentral Wnt signalling networks in human liver homoeostasis: On both, the epigenetic and transcriptional level, we identify a composed network of regulatory changes affecting selected members of the pathway but not a global upregulation or activation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key role of Wnt signaling for the maintenance of liver structure and regeneration is well established from murine liver 12,[27][28][29][30] . A recent analysis indicated that Wnt pathways are also involved in human liver zonation 19 . Our deep integrated datasets allowed a deeper look into the putative role of pericentral Wnt signalling networks in human liver homoeostasis: On both, the epigenetic and transcriptional level, we identify a composed network of regulatory changes affecting selected members of the pathway but not a global upregulation or activation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical analyses have confirmed the zonal distribution of metabolic enzymes, such as cytochrome P450 13,14 , alcohol dehydrogenase 15 , fatty acid-binding protein 16 , glucose-6phosphatase and glutamine synthetase 17 in human liver. Relevant questions, such as the link of metabolic zonation to underlying morphogens, a global assessment of zonation and the underlying regulatory mechanisms and not least also the relation of rodent findings to human liver 18 are as yet not fully addressed 19 .…”
mentioning
confidence: 99%
“…The clusters of hepatocyte that belong to each zonation have distinct functionalities, which lead to the functional compartmentalization of hepatocytes to support the multifaceted function of the liver. 49 To date, assessment of HLCM in the context of the proper formation of hepatic zonation has largely remained elusive and controversial. For example, a study with the FRG-based system suggested that the liver of HLCM failed to form the hepatic zonation based on their mathematical assessment of the pharmacokinetics.…”
Section: Recreation Of Human Liver Physiology At the Organ System Levmentioning
confidence: 99%
“…Wnt signaling pathways are evolutionarily conserved and implicated in the processes of cell fate determination, such as cell differentiation, proliferation, and apoptosis during cell development [10]. To date, three Wnt signaling pathways have been revealed, including the canonical Wnt/β-catenin pathway, the noncanonical Wnt/Ca 2+ pathway, and the Wnt/planar cell polarity (PCP) pathway [11]. The canonical Wnt/β-catenin pathway plays an important role in the regulation of bone formation and has become a new hotspot in the field of the pathogenesis of skeletal diseases and bone metabolism [12,13].…”
Section: Introductionmentioning
confidence: 99%